Constructional collection theory: A critical theoretical perspective for the duality of construction and action - Alkhalifah, Fadiyah Abdullah (Journal of Humanities & Social Sciences, 2020)
This paper sought to identify why Antony Gednaz formulated the theory of constructional collection and the relationship with major theories (structural-functional, Marxism) and minor theories (symbolic interactive) through contrasting and comparing them as well as the comparison between the concept of social symmetry in the verb theory by Parsons and the constructional collection by Gednaz. The paper tried to identify the most important concepts and principles of the constructional collection theory, through a review of the literature in the books of social theories. The paper also included the critical vision of the (female) researcher about the constructional collection theory. The paper concluded that (Antony Gednaz) formulated the constructional collection theory to fill the outstanding gap between structure and action in both major and minor theories and that Gednaz opposes the idea of studying societies based on construction in major theories, and the idea of relying on the action as a unit of study societies in minor theories. He believes that the principal area to study societies is the social practices regulated through time and place. For a social system, Parsons views the system as a group of individual actors, ignoring spatial and temporal conditions that may affect the actions of individuals, while Gednaz sees the system as the sum of acts that are reproduced among the actors in a given place and time. The concept of the constructional collection is the main concept in the collection theory, which means that the collection of actors and buildings are not independent phenomena (i.e. dual), but they represent duplication. In the critical review of the (female) researcher is taken on the central idea of the constructional collection theory that it is not possible to generalize the possibility of reproducing construction. The generalization may be become possible in case replacing the idea of "reproducing construction" by the idea of "modifying construction or parts of construction" or determining what kind of buildings can be reproduced or not. The (female) researcher fully agrees with the idea that the verb produces the structure and after it forms the structure, the structure becomes an intermediary.